2022
DOI: 10.46218/tshd.1136869
|View full text |Cite
|
Sign up to set email alerts
|

Bağimlilik Tedavi̇si̇ Alaninda Kli̇ni̇k Sosyal Hi̇zmet Süpervi̇zonu: Mesleki̇ Geli̇şi̇m, Yeterli̇li̇kler Ve Süpervi̇zyonun Önemi̇

Abstract: Bağımlılık alanında sosyal hizmet mesleği tanı, tespit, tedavi ve sonrası tüm aşamalarda birey ve çevresinin bütüncül değerlendirilmesi açısından kilit öneme sahiptir. Mesleki uygulamalar güncel politika, sosyoekonomik gelişmeler ve kanıt temelli araştırmalarla sürekli değişim göstermektedir. Bu durum bağımlılık alanında sosyal hizmet uzmanları da dâhil profesyonellerin mesleki yetkinliklerinin geliştirilmesini öne çıkarmaktadır. Süpervizyon mesleki yetkinliklerin bilgi, beceri ve değerler odağında geliştirilm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…As a matter of fact, the conclusions that the Ministry entered the earthquake area with as much personnel and resources as possible and did not hesitate to make any sacrifices in supporting the earthquake victims were confirmed by social workers operating in Hatay. It was reported that there was a serious lack or inadequacy of coordination after the Marmara earthquake (Karataş, 2000;Tapan, 2023). This reveals that similar results were obtained with this study conducted in Hatay and that it is compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As a matter of fact, the conclusions that the Ministry entered the earthquake area with as much personnel and resources as possible and did not hesitate to make any sacrifices in supporting the earthquake victims were confirmed by social workers operating in Hatay. It was reported that there was a serious lack or inadequacy of coordination after the Marmara earthquake (Karataş, 2000;Tapan, 2023). This reveals that similar results were obtained with this study conducted in Hatay and that it is compatible with the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Similar findings emerged in Aktaş's (2003) study, in which he investigated how social work intervention would be in crisis situations, the steps of intervention, and the interventions to be carried out at the social level. In a study comparing the Van and Marmara earthquakes in terms of social service activities, it is evaluated that the special needs of vulnerable groups (especially children, women and disabled people) were not adequately addressed and the desired level of psychosocial support was not reached (Altun, 2016;Tapan, 2023). This situation is partially compatible with this research.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations